2013
DOI: 10.3109/00207454.2013.826658
|View full text |Cite
|
Sign up to set email alerts
|

Role of inactivated influenza vaccine in regulation of autoimmune processes in experimental autoimmune encephalomyelitis

Abstract: Experimental autoimmune encephalomyelitis (EAE) is characterized by appearance of anti-myelin autoantibodies in the blood and with the increased expression of MHC (major histocompatibility complex) class I and II antigens in the brain tissue. Although there is an evidence of possible linkage between influenza vaccination and development of autoimmune processes, the precise mechanisms of action of this vaccine on EAE-induction is still unclear. In this study, effects of influenza vaccine on clinical sign, antim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 42 publications
0
2
0
1
Order By: Relevance
“…No difference was found between influenza vaccine vaccinated vs intact groups and a positive correlation was found between anti-MOG antibody titer and the development of the EAE clinical signs. The overall data presented in this study indicate that influenza vaccine has no effect on production of autoantibodies and development of clinical signs 76 . A number of cohort studies demonstrated a transient change in autoantibody production, with presumably no clinical significance, after influenza vaccination in apparently healthy participants 83,84 .…”
Section: Influenza Infection or Vaccination As Probable Trigger Of Msmentioning
confidence: 60%
See 1 more Smart Citation
“…No difference was found between influenza vaccine vaccinated vs intact groups and a positive correlation was found between anti-MOG antibody titer and the development of the EAE clinical signs. The overall data presented in this study indicate that influenza vaccine has no effect on production of autoantibodies and development of clinical signs 76 . A number of cohort studies demonstrated a transient change in autoantibody production, with presumably no clinical significance, after influenza vaccination in apparently healthy participants 83,84 .…”
Section: Influenza Infection or Vaccination As Probable Trigger Of Msmentioning
confidence: 60%
“…He also argues against a general immune stimulation by influenza vaccination since no increase of myelin protein-reactive T-cells was observed after immunization. The overall data presented in this study support the effectiveness and safety of influenza vaccination in the patients with MS. Our group was reported that antiinfluenza antibody titers in healthy vaccinated mice and in MOG induced EAE-vaccinated mice, 4 weeks after vaccina-tion with inactivated influenza vaccine (split virion), was significantly higher compared to the unvaccinated control groups, indicating long-lasting antibody response as well as preserved immune response in MOG induced EAE mice 76 . A possible role of several viruses, including influenza A virus, was investigated in a case-control study in 152 children with MS and a significantly higher concentration of antibodies was found in the MS patients comparing with controls.…”
Section: Influenza Infection or Vaccination As Probable Trigger Of Msmentioning
confidence: 92%
“…La incidencia de complicaciones neurológicas graves post vacuna anti-influenza, incluyendo la EMAD, es muy baja y ha sido estimada en menos de 0,01% en un estudio prospectivo de 49.138 inmunizaciones en una población militar en Francia, lo que nuevamente debilita su rol causal 30 . Por otra parte, un estudio experimental reciente no mostró diferencias significativas en los títulos de anticuerpos antimielina en el grupo vacunado contra influenza al compararlo con controles 31 , lo que disminuye su plausibilidad biológica. Algunos han considerado que debe existir una relación temporal clara entre la inmunización y la aparición del cuadro de EMAD y que la limita a un plazo de una a tres semanas (máximo un mes).…”
Section: Aspectos Patogénicosunclassified